Badania właściwości fizyko-chemicznych oraz fazowych wybranych odpadów przemysłowych w aspekcie ich wykorzystania - Waga, Piotr (My University, 2016)
W ramach pracy przeprowadzono badania podstawowych właściwości fizykochemicznych i fazowych próbek granulowanego żużla wielkopiecowego pochodzących z dwóch krajowych hut stali, pod kątem zagrożenia wymywaniem z nich substancji niebezpiecznych. Próbki żużla różniły się między sobą niektórymi właściwościami fizykochemicznymi, oraz zawartością niektórych składników. Testy wymywania wodnego i TCLP nie wskazały na znaczące zagrożenie migracji zanieczyszczeń z odpadów do środowiska. Metale ciężkie w żużlach znajdują się głównie we frakcjach siarczkowych, oraz rezydualnych, a metalem o największej koncentracji jest Zn2+. Obrazy dyfrakcyjne wskazują na dużą zawartość szkliwa w próbkach. Oprócz dominującego kierunku wykorzystania żużli jakim jest przemysł cementowy, wskazano na inne alternatywne możliwości jego wykorzystania, takie jak sorpcja metali ciężkich czy synteza geopolimerów.

In the dissertation, analysis of the selected physico-chemical and phase properties of the ground granulated blast-furnace slag (GGBFS) derived from two steel plants in Poland was conducted in order to determine environmental risk associated with potential leaching of the pollutants contained in waste. Physico-chemical properties of the examined slag varied within the samples. Aqueous leaching and TCLP test indicated no major environmental risk regarding the migration of pollutants from the wastes. Heavy metals in slag from both installations were bound mostly in sulfides forms, as well as in residual fraction. Zink was found to be the most mobile of all investigated heavy metals. X-ray diffraction patterns indicated high amount of amorphous phase in both samples. Except for cement production, other alternative possibilities of GGBFS utilization was proposed, like heavy metal sorption or synthesis of geopolymers.
Evaluation of the physico-chemical parameters and phase analysis of the selected industrial waste in terms of its utilization
Keywords: huta stali; granulowany żużel wielkopiecowy; badanie fizykochemiczne; badanie fazowe; wykorzystanie przemysłowe; steel plant; granulated blast-furnace slag; physicochemical analysis; phase analysis; utilisation